Styrene-Butadiene Rubber Electrolytes Modified with CaCl2, CdCl2, CuCl2, MnCl2 and Active Carbon - BOROWSKI, TOMASZ (Asian Journal of Chemistry, 2010)
Styrene-butadiene rubber (SBR), as a solvent and repository of electric charges, starts to gain these properties after adding to SBR CaCl2, CdCl2, CuCl2 or MnCl2 in methanol solution with addition of active carbon. Electrical conductivity of such an SBR-active carbon system with added CaCl2 or CdCl2 or CuCl2 or MnCl2 equals to 10-6 to 10-5 S cm-1 at a room temperature (293 K) and a frequency of 10 KHz. The electrolytes were tested for the frequency range of 1 Hz to 25 KHz. These polymer electrolyte systems may find their application as materials for anticorrosive and antielectrostatic protection of fuel or hazardous material tanks.